2024
DOI: 10.3171/2023.5.jns23203
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing geographic gender disparity in neurosurgery: a nationwide geospatial clustering analysis

Abstract: OBJECTIVE Women neurosurgeons (WNs) continue to remain a minority in the specialty despite significant initiatives to increase their representation. One domain less explored is the regional distribution of WNs, facilitated by the hiring practices of neurosurgical departments across the US. In this analysis, the authors coupled the stated practice location of WNs with regional geospatial data to identify hot spots and cold spots of prevalence and examined regional predictors of increases and decreases in WNs ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies across the globe have revealed the various barriers (Fig. 1 ) that impede women’s entry into neurosurgery, notably in academic settings, including the lack of role models, gender discrimination concerns, and work-life balance challenges 3 , 4 , 8 , 11 14 , 15 , 16 . A survey conducted amongst medical students in India revealed that the most common (87.4%) barrier to pursuing neurosurgical residency was lacking prospects and inadequate mentorship, whereas 65.2% of students voted it as an absence of a female role model 15 .…”
mentioning
confidence: 99%
“…Studies across the globe have revealed the various barriers (Fig. 1 ) that impede women’s entry into neurosurgery, notably in academic settings, including the lack of role models, gender discrimination concerns, and work-life balance challenges 3 , 4 , 8 , 11 14 , 15 , 16 . A survey conducted amongst medical students in India revealed that the most common (87.4%) barrier to pursuing neurosurgical residency was lacking prospects and inadequate mentorship, whereas 65.2% of students voted it as an absence of a female role model 15 .…”
mentioning
confidence: 99%